Clinical Pulmonary Research (Neuroscience and Respiration ;, 2018)
This book describes various aspects of current scientific interest in clinical developments and management of pulmonary pathologies. Non-communicable and communicable disorders are tackled. Chronic disorders of an inflammatory background, such as COPD and asthma, often overlapping, diagnostically and therapeutically misguided and always difficult to manage, are in focus due to an increasing prevalence across the age range. The authors dwell on the disease management, exacerbations, care and therapy, taking into account all too often overlooked psychosomatic determinants. Novel markers of pulmonary sarcoidosis, also an inflammatory disease, albeit of unknown etiology, are described. The outstanding lung images of cystic fibrosis are presented in another chapter. Finally, there are reports on the extent of the influenza scourge in Poland during the past 2016/2017 epidemic season. The book is addressed to clinicians, family physicians, medical scholars, and all professionals engaged in the preservation of respiratory health.